Investigation on Light Structural View by Using of Reinforced Concrete with Nanoparticles - Seyyedeh Fatemeh Khoshkalam Soleymandarabi; Raheleh Rostami (Journal of Global Pharma Technology, 2017)
The fibrous concrete is widely used in the construction industry, especially physical appearance industry. In this technical paper has been investigated concrete contained with nanomaterial and their properties.Spraying and pre-mixing techniques for the production have been introduced. If the fiber content is high then trapped air will increase and the density will decrease and thus the weight of parts will reduce. The dimensions of nanoparticles can play the role of filling cavities. Nano crystalline formation can also improve concrete strength. In this paper are introduced self-cleaning concrete, self-monitoring concrete, Nano-reinforced concrete and concrete Nano-coatings and glass Nano-fibers. Finally, in this paper has been paid to the application of fibrous concrete at the international conferences center of Esfahan in Iran and feature of Marriott hotel in San Francisco and the view of the Jubille church in Roma, Italy.Studies have shown that fiber concrete has use in the construction industry because of high-speed production, installation and high flexibility. Kiywords: Fibrous concrete, Nanoparticles, architecture, Self-cleaning concrete, Self-healing concrete, self-monitoring concrete.